Design and development of dual functional Go-Kart seat - Muhammad Firdaus Mohd Ratmin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project aims to design seat based on ergonomics characteristics and to make the seat has suspension system to isolate the vibration due to surface roughness. This is because the flaw of the product become inconvenient to the driver such as the length of the pedal, length from seat to steering and seat would not suitable their best as they driving and the other problem is the go kart has no suspension. The questionnaires have been distributed to the public and go-kart playground to who are already familiar with the go kart to get the best result of survey. The results of questionnaire are very important as to know the problem of go kart that they have been used to the next process to make the analysis. The final concept design is been identified by using Quality Function Deployment (QFD) methods that consist of house of tools, scoring method, and screening method.. The CAD drawing of the project also been done to make the static analysis simulation in the CATIA software. The analyses have been done such as Finite Element Analysis (FEA), costing analysis and ergonomic. The simulation of the CATIA and ergonomic analysis (RULA), the redesign is much better than the existing design in terms of application and the comfortable of the driver.